Der Thesaurusgedanke im Grimmschen Wörterbuch - Schlaefer, Michael (Lexikos, 1994)
The Thesaurus Concept in Grimm's German DictionaryUsers often expect to find a complete collection of German vocabulary and quotations in Grimm's German Dictionary. These opinions result from different pretensions of Grimm lexicographers to produce a thesaurus. A historical analysis allows us to discern four different thesaurus concepts in the development of the German Dictionary. During the first period the concept was determined by the attempts of J. Grimm to document the richness of the entire German language in only one dictionary. With regard to certain puristic selections this thesaurus concept can be described as a 'regulated selected richness'. In the following period regulating elements were replaced by philological scientific methods to give reasons for the maintenance of what R. Hildebrand called internal completeness. The new scientific argument of completeness is the basis for the rise of the German Dictionary to the state of a national thesaurus as well as the slowing down of production. Due to this the dictionary lost part of its acceptance, and the planning of an alternative thesaurus was started. When, in 1908, the Prussian Academy took charge of the German Dictionary the third period of the thesaurus concept, which included several reforms, began. Above all, the claim for completeness was limited to the variety of cultivated speech. These reforms, however, could only solve part of the problems. It was impossible to produce complete articles on philological standards and to finish the dictionary in an adequate time. With the new edition of the German Dictionary, started in 1957, these problems continued. Since 1987 the office in Göttingen tries to go new ways by separating the functions of a dictionary from the functions of a thesaurus. This fourth concept is based on a functional separation between selective dictionary articles and a complementary data-based register of texts. Keywords: academy dictionaries, collection of quotations, conception, dictionary, dictionary entries, dictionary planning, dictionary styles, dictionary users, grimm's dictionary, history of dictionaries, thesaurus